2014
DOI: 10.1371/journal.pone.0086487
|View full text |Cite
|
Sign up to set email alerts
|

Land Use Compounds Habitat Losses under Projected Climate Change in a Threatened California Ecosystem

Abstract: Given the rapidly growing human population in mediterranean-climate systems, land use may pose a more immediate threat to biodiversity than climate change this century, yet few studies address the relative future impacts of both drivers. We assess spatial and temporal patterns of projected 21st century land use and climate change on California sage scrub (CSS), a plant association of considerable diversity and threatened status in the mediterranean-climate California Floristic Province. Using a species distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(42 citation statements)
references
References 78 publications
2
40
0
Order By: Relevance
“…In contrast to our expectations, land use change was primarily brought about by soil subsidence in response to the sustained management of lower water levels and hardly driven by additional effects of climate change. These findings are in concordance with Riordan and Rundel (2014), who found that projected land use change was a more important driver of habitat loss for plant species than climate change in a Californian ecosystem. Because our study focuses on the impact of climate change on local habitat quality and bird densities rather than range shifts, we did not include climate envelope modeling in our study, but restricted ourselves to habitat modeling only.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In contrast to our expectations, land use change was primarily brought about by soil subsidence in response to the sustained management of lower water levels and hardly driven by additional effects of climate change. These findings are in concordance with Riordan and Rundel (2014), who found that projected land use change was a more important driver of habitat loss for plant species than climate change in a Californian ecosystem. Because our study focuses on the impact of climate change on local habitat quality and bird densities rather than range shifts, we did not include climate envelope modeling in our study, but restricted ourselves to habitat modeling only.…”
Section: Discussionsupporting
confidence: 92%
“…A large scale switch to bioenergy crops may lead to significant landscape changes (Gaucherel et al 2010). Although it is increasingly recognized that projections of climate change impacts on ecological network quality also should include effects of autonomous land use changes (Barbet-Massin et al 2012;Van Teeffelen et al 2012;Jongsomjit et al 2013;Riordan and Rundel 2014), land use changes driven by climate change itself are rarely taken into account (but see Bakker et al 2014). The relative impact of such indirect effects of climate change on the quality of ecological networks therefore remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Because many of the remaining SS fragments are threatened by type-conversion to non-native grasslands and/or conversion to suburban/urban habitats by future development (Cox et al 2014;Goldstein and Suding 2014;Kimball et al 2014;Riordan and Rundel 2014), understanding how such landscape transformations influence arthropod biodiversity is critical to conservation efforts at multiple scales. On a local scale, our research demonstrates that conversion of SS to non-native grassland will favor a unique subset of native ant species, while conversion to suburban habitat favors a surprisingly diverse but overwhelmingly non-native ant fauna.…”
Section: Discussionmentioning
confidence: 99%
“…The resulting development and habitat modification make Mediterranean ecosystems some of the most threatened worldwide (Sala et al 2000). This is especially true in southern California and northern Mexico, which have more than double the human population density of any other Mediterranean region (Underwood et al 2009;Riordan and Rundel 2014). Moreover, southern California's human population is disproportionately concentrated in its lowlands, 20 % of which are now urban, with much of the rest suburban, agricultural, or otherwise disturbed (Underwood et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Source: Modified from: Schmitt (2011 Another issue is the loss of habitat structure that generally leads to a decline in species richness and biomass. The combined impacts of climate change and land use are expected to drive unprecedented rates of environmental change and biodiversity loss (Riordan and Rundel, 2014). In particular, climate change is likely to have a large impact on biodiversity, from organisms to biomes (see Bellard et al, 2012 for a exhaustive review).…”
Section: Biodiversity Conservation and Prioritiesmentioning
confidence: 99%